Post-Socialist Culture and Entrepreneurship - Petrik Runst (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In this paper it is argued that locus of control beliefs and preferences concerning state action negatively affect the formation of new firms in former socialist countries. For this purpose Kirzner's theory of costless entrepreneurship is reviewed and criticized. German reunification, in which the formerly Socialist East joined the Federal Republic of Germany, represents an intriguing natural experiment in which the formal institutional structure of one nation was almost fully transplanted into another. Traditional as well as psychological factors are examined. The results suggest that about one third of the east-west gap in new self-employment can be explained by inert informal institutions.
Keywords: D0; J24; O12; P20; 330; Psychology of Entrepreneurship; Self-Employment; Transitional Economies; East Germany; Entrepreneurship-Ansatz; Unternehmer; Verhaltensökonomik; Unternehmensgründung; Systemtransformation; Ostdeutschland